Comparison of digital subtraction angiography, micro-computed tomography angiography and magnetic resonance angiography in the assessment of the cerebrovascular system in live mice - Negrão de Figueiredo Miller, Giovanna; Brockmann, Carolin; Boll, Hanne; Heilmann, Melanie; Schambach, Sebastian Jobst; Fiebig, Anna Teresa; Groden, Christoph; Brockmann, Marc Alexander (Clinical neuroradiology, 2012)
PurposeMice are often used as small animal models of brain ischemia, venous thrombosis, or vasospasm. This article aimed at providing an overview of the currently available methodologies for in vivo imaging of the murine cerebrovasculature and comparing the capabilities and limitations of the different methods.MethodsMicro-computed tomography angiography (CTA) was performed during intra-arterial and intravenous administration of a contrast agent bolus. Digital subtraction angiography (DSA) was performed during intra-arterial administration of contrast agent using the micro-CT scanner. Time-of-flight (ToF) magnetic resonance (MR) angiography was performed using a small animal scanner (9.4 T) equipped with a cryogenic transceive quadrature coil. Datasets were compared for scan time, contrast-to-noise ratio (CNR), temporal and spatial resolution, radiation dose, contrast agent dose and detailed recognition of cerebrovascular structures.ResultsHighest spatial resolution was achieved using micro-CTA (16 ´ 16 ´ 16 µm) and DSA (14 ´ 14 µm). Compared to micro-CTA (20-40 s) and ToF-MRA (57 min), DSA provided highest temporal resolutions (30 fps) allowing analyses of the cerebrovascular blood flow. Highest mean CNR was reached using ToF-MRA (50.7 ± 15.0), while CNR of micro-CTA depended on the intra-arterial (19.0 ± 1.0) and intravenous (1.3 ± 0.4) use of agents. The CNR of DSA was 10.0 ± 1.8.ConclusionsThe use of dedicated small animal scanners allows cerebrovascular imaging in live animals as small as mice. As each of the methods analyzed has its advantages and limitations, choosing the best suited imaging modality for a defined question is of great importance. By this means the aforementioned methods offer a great potential for future projects in preclinical cerebrovascular research including ischemic stroke or vasospasm.